2002
DOI: 10.1128/jvi.76.8.3756-3764.2002
|View full text |Cite
|
Sign up to set email alerts
|

Membrane Recognition by Vesicular Stomatitis Virus Involves Enthalpy-Driven Protein-Lipid Interactions

Abstract: Vesicular stomatitis virus (VSV) infection depends on the fusion of viral and cellular membranes, which is mediated by virus spike glycoprotein G at the acidic environment of the endosomal compartment. VSV G protein does not contain a hydrophobic amino acid sequence similar to the fusion peptides found among other viral glycoproteins, suggesting that membrane recognition occurs through an alternative mechanism. Here we studied the interaction between VSV G protein and liposomes of different phospholipid compos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
81
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 91 publications
(88 citation statements)
references
References 58 publications
(63 reference statements)
5
81
1
Order By: Relevance
“…Membrane fusion mediated by VSV G protein reconstituted in lipid vesicles showed a large preference for target membranes containing PS or phosphatidic acid (42). We found that the extent of pHinduced conformational changes of G protein depends on the number of negative charges in the target membrane and that G protein-mediated membrane fusion may be correlated with the PS content in the vesicles (35). Although our results unequivocally demonstrate the importance of electrostatic interactions for VSV fusion, we cannot exclude the possibility that hydrophobic interactions are also involved in VSV interaction with membranes during fusion.…”
Section: Role Of Phosphatidylserinecontrasting
confidence: 42%
See 4 more Smart Citations
“…Membrane fusion mediated by VSV G protein reconstituted in lipid vesicles showed a large preference for target membranes containing PS or phosphatidic acid (42). We found that the extent of pHinduced conformational changes of G protein depends on the number of negative charges in the target membrane and that G protein-mediated membrane fusion may be correlated with the PS content in the vesicles (35). Although our results unequivocally demonstrate the importance of electrostatic interactions for VSV fusion, we cannot exclude the possibility that hydrophobic interactions are also involved in VSV interaction with membranes during fusion.…”
Section: Role Of Phosphatidylserinecontrasting
confidence: 42%
“…This indicates that the protonation of a small number of ionizable groups is required for G protein structural changes, suggesting that the protonation of the imidazole ring of histidyl residue(s) (pK = 6.0) is involved in G protein conformational changes required for fusion. In addition, we have found that VSV binding to membranes as well as the fusion reaction itself were highly dependent on electrostatic interactions between negative charges on the membrane surface and positively charged amino acids in G protein at the fusion pH (35), and His becomes positively charged after protonation ( Figure 3). For rabies virus, Roche and Gaudin (43), showed that the pK of the transition from the native to the fusion-inactive state of G protein is 6.65, also suggesting that His residues are involved.…”
Section: Role Of Histidinesmentioning
confidence: 99%
See 3 more Smart Citations